2004
DOI: 10.1103/physreva.69.030301
|View full text |Cite
|
Sign up to set email alerts
|

Dispersive manipulation of paired superconducting qubits

Abstract: We combine the ideas of qubit encoding and dispersive dynamics to enable robust and easy quantum information processing (QIP) on paired superconducting charge boxes sharing a common bias lead. We establish a decoherence free subspace on these and introduce universal gates by dispersive interaction with a LC resonator and inductive couplings between the encoded qubits. These gates preserve the code space and only require the established local symmetry and the control of the voltage bias.PACS numbers: 03.67. Lx,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…15,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32 In particular, the promising design being developed at Yale, 15,28,29 using charge qubits coupled to superconducting transmission line resonators, is very similar to the architecture discussed here. Each junction is connected to a metallic plate on the surface of the resonator that covers about one quarter of the surface.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…15,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32 In particular, the promising design being developed at Yale, 15,28,29 using charge qubits coupled to superconducting transmission line resonators, is very similar to the architecture discussed here. Each junction is connected to a metallic plate on the surface of the resonator that covers about one quarter of the surface.…”
Section: Discussionmentioning
confidence: 88%
“…Several investigators have proposed the use of LC resonators, 17,18,19,20,21,22,23,24,25,26 superconducting cavities, 15,27,28,29 or other types of oscillators, 30,31,32 to couple JJs together. We note that although harmonic oscillators are ineffective as computational qubits, because the lowest pair of levels cannot be frequency selected by an external driving force, they are quite desirable as bus qubits or coupling elements.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the dephasing effects are usually stronger than the relaxation ones [33], the present encoded scheme is just immune to the σ ztype collective dephasing effects, which is helpful to enhance the fidelity. It is found that the dephasing time of the encoded logic qubits may be prolonged to two orders of magnitude longer using well-designed charge qubits with same device parameters [18,31].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, encoding qubits into decoherence-free subspace (DFS) is an interesting way to avoid quantum errors [18][19][20][21]. Towards implementing the fault-tolerant schemes, the controllable interqubit couplings and the optimal quantum operations are two important aspects.…”
mentioning
confidence: 99%
“…Such encoding is also attractive for superconducting charge qubits, 6,7 which are subject to similar decoherence sources. 8 In this work, we show how to develop such protection for qubits coupled by the nearest neighbor XY-interaction that is encountered in both flux and charge qubit designs.…”
mentioning
confidence: 99%